Sistem Pakar Diagnosa Covid-19 Menggunakan Metode Forward Chaining Berbasis Mobile - Budiyanto, Agus; Mubarok, Roy (CV. Shofanah Media Berkah, 2024)
An expert system is a computer-based system that uses knowledge, facts and reasoning techniques in solving problems that can usually only be solved by an expert in that field. The implementation of expert systems is widely used for commercial purposes because the expert system is seen as a way of storing expert knowledge in a particular field into computer programs and is designed in such a way that it can give decisions and make intelligent reasoning. One implementation that can be applied is in the world of health. In addition to bE1ng a medium of information for the public but also can provide an early diagnosis of the disease that is usually only an expert who can explain about the disease. COVID-19 is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 can cause respiratory system disorders, ranging from mild symptoms such as flu, to lung infections, such as pneumonia. COVID-19 (coronavirus disease 2019) is a new type of disease caused by the coronavirus group, SARS-CoV-2 which is also often called Corona virus. The first case of the disease occurred in wuhan city, China, in late December 2019. After that, COVID-19 spread between people very quickly and spread to dozens of countries, including Indonesia, in just a few months. To reduce the spread and make it easier to diagnose these symptoms I tried to create an application that can facilitate the diagnosis of Covid-19. With this application I wholeheartedly want the transmission of Covid-19 is resolved immediately, because it is known earlier indications of the virus.